Clinical and Vitamin Response to a Short‐Term Multi‐Micronutrient Intervention in Brazilian Children and Teens: From Population Data to Interindividual Responses. Issue 6 (22nd February 2018) - Mathias, Mariana Giaretta; Coelho‐Landell, Carolina de Almeida; Scott‐Boyer, Marie‐Pier; Lacroix, Sébastien; Morine, Melissa J.; Salomão, Roberta Garcia; Toffano, Roseli Borges Donegá; Almada, Maria Olímpia Ribeiro do Vale; Camarneiro, Joyce Moraes; Hillesheim, Elaine; de Barros, Tamiris Trevisan; Camelo‐Junior, José Simon; et al.
Abstract : Scope: Micronutrients are in small amounts in foods, act in concert, and require variable amounts of time to see changes in health and risk for disease. These first principles are incorporated into an intervention study designed to develop new experimental strategies for setting target recommendations for food bioactives for populations and individuals. Methods and results: A 6‐week multivitamin/mineral intervention is conducted in 9–13 year olds. Participants (136) are (i) their own control ( n ‐of‐1); (ii) monitored for compliance; (iii) measured for 36 circulating vitamin forms, 30 clinical, anthropometric, and food intake parameters at baseline, post intervention, and following a 6‐week washout; and (iv) had their ancestry accounted for as modifier of vitamin baseline or response. The same intervention is repeated the following year (135 participants). Most vitamins respond positively and many clinical parameters change in directions consistent with improved metabolic health to the intervention. Baseline levels of any metabolite predict its own response to the intervention. Elastic net penalized regression models are identified, and significantly predict response to intervention on the basis of multiple vitamin/clinical baseline measures. Conclusions: The study design, computational methods, and results are a step toward developing recommendations for optimizing vitamin levels and health parameters for individuals. Abstract : Identical 6‐week multivitamin/mineral interventions are conducted in successive years in adolescents. Data are aggregated for population level analysis and for individual responses. Most levels of plasma vitamins respond positively and many clinical parameters change in directions consistent with improved metabolic health to the intervention. Elastic net models significantly predict response to intervention on the basis of multiple vitamin/clinical baseline measures.